1999
DOI: 10.1023/a:1007700326811
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To evaluate the effect of manidipine 10 mg on 24-hour ambulatory blood pressure (BP) and heart rate (HR) in very elderly hypertensive patients, 54 patients aged 76-89 years (mean age 81.8 years) with systolic blood pressure (SBP) > 160 mmHg and diastolic blood pressure (DBP) > 90 mmHg were studied. After a 4-week placebo washout period, patients were randomized to receive manidipine 10 mg or placebo, both administered once daily for 8 weeks. Patients were checked after the initial run-in placebo phase and ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this group, manidipine, 2-[4-(diphenylmethyl)-1-piperazinyl]ethylmethyl(±)-1, 4-dihydro-2, 6-dimethyl-4-(m-nitrophenyl)-3, 5-pyridinedicarboxylate (Figure 1), stands out as a third-generation calcium channel blocker, effective for treating high blood pressure even to elderly people or patients with associated diseases such as diabetes and nephropathy [35]. …”
Section: Introductionmentioning
confidence: 99%
“…In this group, manidipine, 2-[4-(diphenylmethyl)-1-piperazinyl]ethylmethyl(±)-1, 4-dihydro-2, 6-dimethyl-4-(m-nitrophenyl)-3, 5-pyridinedicarboxylate (Figure 1), stands out as a third-generation calcium channel blocker, effective for treating high blood pressure even to elderly people or patients with associated diseases such as diabetes and nephropathy [35]. …”
Section: Introductionmentioning
confidence: 99%
“…Manidipine is a third generation dihydropyridine calcium channel blocker that effectively reduces BP levels with a sustained effect over 24 hours, without a significant increase of heart rate or cardiac output [ 70 ]. Different studies have analyzed the antihypertensive efficacy of manidipine [ 68 , 69 , 71 82 ]. These studies have shown that manidipine reduces BP levels to a similar extent than enalapril, lisinopril or amlodipine, among other antihypertensive drugs.…”
Section: Manidipine: Beneficial Effects Beyond Blood Pressure Controlmentioning
confidence: 99%